Peningkatan Literasi Keuangan dan Manajemen Diri bagi Young Entrepreneurs Mahasiswa Politeknik Negeri Ujung Pandang - Maryam Nadir; Rasyidah Nadir; Tawakkal Tawakkal; Kartini Kartini (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
Financial Literacy is a crucial aspect in supporting the success of a business for young entrepreneurs, especially in preparing financial reports. Financial literacy encompasses knowledge of money management, investment, and financial planning, while self-management encompasses skills such as time discipline, emotional control, and decision-making. "Improving Financial Literacy and Self-Management for Young Entrepreneurs of Polytechnic Students" has successfully achieved its primary objective with significant achievements. The general objective was achieved through a 25-30% increase in financial literacy and self-management scores, enabling students to manage their businesses more effectively and sustainably. Specific objectives were also met: workshops provided basic knowledge, mentoring trained practical skills, and the application of the concept of forming an aware community. Positive impacts were seen in reducing business risks and contributing to the polytechnic's entrepreneurial ecosystem. Positive impacts resulting from this program include reducing business risks and contributing to the development of the entrepreneurial ecosystem at the Polytechnic. This program is expected to become a model that can be applied in other educational institutions to support the development of young entrepreneurs in Indonesia.